2022
DOI: 10.1364/optica.449225
|View full text |Cite
|
Sign up to set email alerts
|

Multi-pass cells for post-compression of ultrashort laser pulses

Abstract: Ultrafast lasers reaching extremely high powers within short fractions of time enable a plethora of applications. They grant advanced material processing capabilities, are effective drivers for secondary photon and particle sources, and reveal extreme light-matter interactions. They also supply platforms for compact accelerator technologies, with great application prospects for tumor therapy or medical diagnostics. Many of these scientific cases benefit from sources with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(37 citation statements)
references
References 153 publications
0
31
0
Order By: Relevance
“…The setup based on pairs of 2 mm and 4 mm thick α-BBO crystal plates is cheap, ultra-compact and completely passively stable. In addition to gas-filled MPCs as presented in this work, DPNLC is expected to allow similar scaling potential for other polarization insensitive MPC schemes as well, including those based on anti-reflective coated bulk nonlinear media [9]. Thus, DPNLC is an extremely powerful extension to easily scale the performance of pre-built MPC-based nonlinear compression stages without requiring a complete rebuilding and, when designing an MPC from scratch, it allows significant reduction of cost and size of the setup.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The setup based on pairs of 2 mm and 4 mm thick α-BBO crystal plates is cheap, ultra-compact and completely passively stable. In addition to gas-filled MPCs as presented in this work, DPNLC is expected to allow similar scaling potential for other polarization insensitive MPC schemes as well, including those based on anti-reflective coated bulk nonlinear media [9]. Thus, DPNLC is an extremely powerful extension to easily scale the performance of pre-built MPC-based nonlinear compression stages without requiring a complete rebuilding and, when designing an MPC from scratch, it allows significant reduction of cost and size of the setup.…”
Section: Discussionmentioning
confidence: 99%
“…The needed parameters are usually generated by a high-power amplifier scheme based on thin-disk, slab or fiber, followed by a nonlinear pulse compression stage to access the sub-100 fs regime [1,4,5]. While different post-compression schemes have been developed over the past decades, recently multipass cell (MPC) based approaches have gained a lot of attention [6][7][8][9]. Typically, MPCs feature a high transmission and are mostly resistant to pointing instabilities of the driving laser, allowing reliable nonlinear compression of kilowatt level average powers [5] and multi-millijoule pulse energies [4].…”
Section: Introductionmentioning
confidence: 99%
“…Over the long term, the development of reliable, high-rep-rate sources in the mid-wave infrared (3-8µm) and long-wave infrared (8-15 µm) could also provide unique opportunities for HEP applications, including as an enabling technology for an "all-optical" source of highbrightness, potentially spin-polarized, electron beams using two-color injection [42,43,64]. Other promising paths include using diode-pumped, cryogenically-cooled, thin-disk Yb:YAG or Tm:YLF as amplifier gain media [65][66][67][68], combined with nonlinear pulse compression technologies [69,70], or novel, plasma-based methods for modulating ps-duration pulses [71]. All candidate laser technologies require development of active control techniques for laser precision and stability [72,73], and high peak and average power handling optics, including compression gratings [74,75] and robust optical coatings [76][77][78].…”
Section: B High-power Laser Randdmentioning
confidence: 99%
“…Shortly after, Daniault et al demonstrated the compression of 30 fs, 1 mJ pulses from a Ti:Sapphire CPA down to 5.2 fs [106], extending implementation of MPC compression of Ti:Sapphire CPAs to the mJ energy range. A recent review about nonlinear pulse compression in MPCs can be found in [107].…”
Section: Post-compression Of High Power Cpasmentioning
confidence: 99%